Distribution of adsorbed water in shale: An experimental study on isolated kerogen and bulk shale samples - Zou, J.; Rezaee, Reza; Yuan, Y.; Liu, K.; Xie, Sam; You, L. (ELSEVIER, 2020)
Bakken shale samples were studied for distribution of adsorbed water using low-pressure nitrogen sorption. By comparing results between dry and wet samples, the distribution of adsorbed water in shale was determined. Two of the isolated kerogen samples show a striking change of pore size distribution (PSD) in large pores (>16 nm), indicating the pronounced distribution of adsorbed water in large pores of organic matter. As for the bulk shale, water can adsorb in both small (<16 nm) and large pores (>16 nm) depending on hydrophilic sites. However, hydrophilic sites in small pores are mainly contributed by inorganic matter, while hydrophilic sites in large pores are composed of inorganic or organic matter. The overall results therefore clarify the contribution of inorganic and organic matter to water adsorption in shale and provide a better understanding of the significance of adsorbed water in shale.